Pengembangan Media Educandy untuk Meningkatkan Literasi Teknologi dalam Mendukung SDGs - Donna Boedi Maritasari; Rifaatul Mahmudah; Siti Mawaddatil Husna Waahluzziadah (Universitas Cokroaminoto Palopo, 2025)
This study aims to develop and validate Educandy-based learning media to enhance students’ technology literacy in line with Sustainable Development Goals (SDGs). The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were 19 third-grade students of SDN 1 Aikmel Timur during the 2024/2025 academic year. Data were collected through observations, interviews, validation sheets, questionnaires, and pretest–posttest instruments. Results of material expert validation obtained a score of 76% (valid), while media expert validation reached 78% (valid). Practicality testing by teachers and students indicated positive responses, with teacher practicality reaching 80% and student practicality 79.75%, categorized as “practical.” Effectiveness testing showed a significant increase in students’ technology literacy, with the average pretest score of 33.26 improving to 86.66 in the posttest. The N-Gain calculation of 80% indicated “effective.” These findings confirm that Educandy-based learning media is valid, practical, and effective in enhancing students’ technology literacy, thereby supporting the achievement of SDG 4 (quality education).